A Retrospective Audit of Pharmacologic and Non-Pharmacologic Management of Childhood Acute Asthma Exacerbation at Usmanu Danfodiyo University Teaching Hospital, Sokoto: Adherence to Global Treatment Guidelines - Oshikoya, Kazeem Adeola; Ogunyinka, Ibrahim Abayomi; Imuzei, Shallom Ese; Garba, Bilkisu Ilah; Jiya, Nma Mohammed (Frontiers in Pharmacology, 2020)
Background Adequate management of childhood acute asthma exacerbation requires optimal non-pharmacotherapy and pharmacotherapy. Global asthma guidelines provide critical information and serves as a quick reference decision-support material for clinicians. Objectives We aimed at evaluating hospital management of childhood acute asthma exacerbation to ascertain its conformity to the global treatment guidelines, and to identify factors that predict short or prolonged observation in the hospital. Method This was a retrospective audit of the management of acute asthma exacerbation in children seen between 01 January 2017 and 31 December 2018 at Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto, Nigeria. Relevant data on demography, asthma triggers and severity, functional and clinical diagnoses, types of controller medications used before and after presentation, non-pharmacotherapy and pharmacotherapy instituted during presentation, duration of observation in the hospital, and treatment outcomes were extracted from the case file of each eligible patient. Results A total of 119 children presented with features of suspected acute asthma exacerbations during the study period but only 63 (52.9%) that met the inclusion criteria for the study were included for analysis. The 63 children that were evaluated had mild (47; 74.6%) and moderate (16; 25.4%) acute asthma exacerbations. Their median (interquartile range) age was 8 (5–15) years. More males (36; 57.1%) than females (27; 42.9%) presented with features of the condition. Majority (50; 79.8%) of the patients had at least one trigger factor and of the 73 trigger factors reported, cold weather (19; 26.0%) was the commonest. Nebulized salbutamol (48; 76.5%), in addition to intravenous (23; 57.9%) and oral (17; 42.5%) corticosteroids, was used during hospital treatment. Patients were discharged mostly on short course of oral corticosteroid only (37; 58.8%). Of the 17 major recommendations in the Global Initiative for Asthma (GINA) guidelines, good (5; 29.4%), moderate (7; 41.2%), and poor (5; 29.4%) levels of adherence were observed. Specifically, moderate and poor levels of adherence were observed in the management of 61(96.8%) and 2(3.2%) patients, respectively. The odds of admission for ≤12 h were higher for female children and patients with mild cases. Conclusion Good and moderate adherence levels to 12 of the 17 GINA recommendations were observed in our center. Nonetheless, reinforcement of institutional guidelines for acute asthma management is suggested to further improve the quality of care of childhood acute asthma exacerbations.